2018
DOI: 10.1038/s41598-018-19878-x
|View full text |Cite
|
Sign up to set email alerts
|

Chirality recognition of winding vine-shaped heterobiaryls with molecular asymmetry. Kinetic and dynamic kinetic resolution by Shi’s asymmetric epoxidation

Abstract: The chirality of winding vine-shaped heterobiaryls with molecular asymmetry is recognized by a sugar-based chiral oxidant. Kinetic resolution of (±)-bisbenzoimidazole bearing an olefin moiety takes place with Shi’s asymmetric epoxidation to observe krel value up to ca. 35 affording the corresponding epoxide. The reaction of a (±)-bithiophene derivative also recognized the chirality to give the corresponding epoxide with er of 96:4 at 39% conversion. Dynamic kinetic resolution is found to take place when unsymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…We have been studying the thus obtained cyclized product, which we name such a kind of chirality as the winding vine-shaped molecular asymmetry. [11] The first preparation was shown with bis(benzo)imidazole [12] and several related hetero [13][14][15] and non-heteroaromatic [16] vine-shaped molecules have also been synthesized. We have also shown that the annulation reactions with nosylated diamine (nosyl: 2-nitrobenzenesulonyl) [17,18] with benzylic halide also furnishes another class of vine-shaped molecules and thus obtained compounds also showed molecular asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the thus obtained cyclized product, which we name such a kind of chirality as the winding vine-shaped molecular asymmetry. [11] The first preparation was shown with bis(benzo)imidazole [12] and several related hetero [13][14][15] and non-heteroaromatic [16] vine-shaped molecules have also been synthesized. We have also shown that the annulation reactions with nosylated diamine (nosyl: 2-nitrobenzenesulonyl) [17,18] with benzylic halide also furnishes another class of vine-shaped molecules and thus obtained compounds also showed molecular asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the thus obtained cyclized product, which we call such a kind of chirality as the winding vineshaped molecular asymmetry. [11] The first preparation was shown with bis(benzo)imidazole [12] and several related hetero [13][14][15] and non-heteroaromatic [16] vine-shaped molecules have also been synthesized. We have also shown that the annulation reactions with nosylated diamine (nosyl: 2-nitro-benzenesulonyl) [17,18] with benzylic halide also furnishes another class of vine-shaped molecules and thus obtained compounds also showed molecular asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…[5] It was also revealed that the obtained product exhibited molecular asymmetry, in which axial, helical, and planar chiralities were involved in the molecule and their inversion of the chirality took place in a synchronized manner. Separation of the enantiomer with HPLC on chiral stationary phase, [3,6] resolution with the preparative column, [3] and enantioselective metathesis [7,8] have been successful to afford the enantiomerically pure/enriched compounds. It was also shown to undergo an additional protocol to afford winding vine-shaped molecules employing annulative nucleophilic substitution with nosyl (2-nitrobenzenesulfonyl) diamines to give vine-shaped biaryl 2.…”
Section: Introductionmentioning
confidence: 99%